22 Impaired stress-induced oxygenation in hypertrophic cardiomyopathy is associated with an increased risk of ventricular arrhythmia. (March 2019) - Raman, Betty; Mahmod, Masliza; Chan, Kenneth; Sivalokanathan, Sanjay; D Karamitsos, Theodoros; Selvanayagam, Joseph; Ariga, Rina; T Hess, Aaron; M Tunnicliffe, Elizabeth; Watkins, Hugh; Neubauer, Stefan
Abstract : Background: Myocardial ischaemia is believed to promote fatal life-threatening ventricular arrhythmias in hypertrophic cardiomyopathy (HCM). Oxygen sensitive cardiac magnetic resonance (CMR) or blood oxygen level dependent (BOLD) imaging can detect blunted myocardial oxygenation during vasodilator stress in HCM. Whether or not impairment in stress oxygenation is associated with ventricular arrythmia risk is unknown. Objectives: To investigate the relationship between blunted stress oxygenation and ventricular arrhythmia in HCM and examine the determinants of stress oxygenation in HCM. Methods: 103 genotyped HCM patients and 32 (age, gender and body mass index matched) healthy controls underwent adenosine stress BOLD, stress first pass perfusion imaging and late gadolinium imaging (LGE) to assess stress oxygenation, myocardial perfusion reserve index (MPRI), and fibrosis burden respectively. Stress oxygenation response (BOLD ΔSI) was estimated as a relative increase in oxygen sensitive BOLD signal intensity from rest to peak vasodilator stress. All HCM patients had 24-holter monitoring to assess for ventricular tachycardia (≥3 beats, ≥120 beats per minute). Results: As expected, both MPRI (1.5±0.4 v 2.0±0.3, p<0.0001) and stress oxygenation (9.1%±4.1% v 17.0%±1.6%, p<0.0001, figure 1C ) were significantly impaired in HCM patients compared to controls. Among HCM patients, twenty six (25%) had ventricular tachycardia and demonstrated more severe impairment in stress oxygenation (6.9%±0.8%) than other patients (9.9%±0.5%, p=0.001). The prevalence of ventricular arrythmia increased with decreasing quartiles of oxygenation (figure 1F ). HCM patients in the lowest quartile of stress oxygenation (BOLD ΔSI≤6.5%) were at a three-fold risk of ventricular arrhythmia (OR 3.04, p=0.04) compared to other patients, despite adjusting for differences in LGE mass and other sudden cardiac death risk factors (table 1 ). Sarcomeric mutation status (β=−2.32, p=0.007) was the only independent predictor of the extent of stress oxygenation after adjusting for univariate confounders (wall thickness, MPRI and LGE mass). Sarcomeric HCM displayed more severe impairment in stress-induced oxygenation than genotype negative HCM and healthy controls (figure 1E ). Conclusion: In HCM, impaired stress-induced oxygenation is associated with an increased risk of ventricular arrhythmia and may represent a novel biomarker of arrhythmic risk. Sarcomeric mutation status independently predicts a blunted stress oxygenation response in HCM.